Empowering Traditional Fisherfolk: Informing on Legal Rights in Marine Biodiversity - Henky Mayaguezz; Yunita Maya Putri; Tristiyanto Tristiyanto; Ria Wierma Putri; Almira Fardani Lahay (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2023)
The government officially recognized the existence of traditional fishermen through Law Number 7 of 2016, focusing on Fisherman Protection and Empowerment. Nevertheless, these traditional fishermen remain an economically disadvantaged group, constrained by their reliance on age-old fishing techniques and practices. This situation hinders their access to vital information about maritime zones, in accordance with UNCLOS'82, and capture fisheries zones. The plight of traditional fishermen in Muara Gading Mas Village, East Lampung, serves as a stark illustration of this reality. The project also includes education on fishing jurisdictions within Indonesian waters. Employing a Community Education method, this service project engages representatives of the Muara Gading Mas fishing community in a discussion forum focused on their rights as traditional fishermen. This initiative aims to boost traditional fishermen's comprehension across various indicators, including marine area zoning, the protection of fishermen's rights, the fishermen protection law, the benefits of counseling for traditional fishermen, and understanding the process of reporting problems encountered by traditional fishermen. Nonetheless, improving the welfare of traditional fishermen in Muara Gading Mas Village necessitates government intervention, particularly in the provision of facilities to enhance their traditional fishing activities.